Unveiling the Impact of Factors on Taxpayer Compliance: Mengungkap Dampak Faktor-Faktor terhadap Kepatuhan Wajib Pajak - Nova Atul Arini; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2024)
Tax compliance significantly impacts tax revenue, with increased compliance correlating to heightened state revenue. This study investigates the influence of taxpayer awareness, taxation understanding, tax sanctions, and tax service quality on tax compliance among motor vehicle taxpayers at the Sidoarjo Samsat Office. The research employs a quantitative descriptive approach, utilizing primary data gathered through questionnaires. The population consists of 955,635 registered taxpayers, with 100 selected through incidental sampling. Findings reveal that taxpayer awareness, taxation understanding, tax sanctions, and service quality positively influence tax compliance. This study addresses a gap in understanding taxpayer behavior and provides insights for policymakers to enhance compliance strategies, thereby optimizing tax revenue. Highlight: Descriptive quantitative approach: Primary data collected via questionnaires. Key findings: Factors affecting tax compliance elucidated. Policy insights: Informing strategies for enhancing tax compliance and revenue. Keywoard: Tax compliance, Awareness, Understanding, Sanctions, Service quality.